1985
DOI: 10.1128/aac.27.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tobramycin and gentamicin in abusers of intravenous drugs

Abstract: The kinetics of aminoglycoside elimination were determined in 18 hospitalized narcotics abusers receiving gentamicin or tobramycin for treatment of severe infection. Rapid aminoglycoside elimination (requiring doses of >5 mg/kg per day to maintain adequate drug levels) was noted in 12 of the 18 patients (18 of 27 clearance studies). Patients found to have rapid elimination were younger (P < 0.01) and had larger drug distribution volumes (P < 0.005), greater measured creatinine clearances (P < 0.05), and lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…We should like to point out, however, that in our study population (which was an unselected population of patients treated with tobramycin) only few patients were morbidly obese. It has been reported that younger patients require a higher loading dose on a mg kg-l basis than older patients (King et al, 1985), a trend seen in our studies. The reason for this age effect is not clear but it may reflect the different distribution of tissue masses as a function of age.…”
Section: Resultssupporting
confidence: 71%
“…We should like to point out, however, that in our study population (which was an unselected population of patients treated with tobramycin) only few patients were morbidly obese. It has been reported that younger patients require a higher loading dose on a mg kg-l basis than older patients (King et al, 1985), a trend seen in our studies. The reason for this age effect is not clear but it may reflect the different distribution of tissue masses as a function of age.…”
Section: Resultssupporting
confidence: 71%
“…The mechanism for enhanced aminoglycoside elimination that results in increased dosage requirements'for burn patients appears to be related to an increased glomerular filtration rate (12,(23)(24)(25). Intravenous drug abusers (IVDA) have also been reported to eliminate aminoglycosides at a rate which necessitates more aggressive aminoglycoside dosage regimens (10). This observation has not been reported with vancomycin' a'dministration in this patient population.…”
mentioning
confidence: 81%
“…Induction of a new metabolic route of elimination may be related to the basic bio-246 chemical defect, the result of repeated infection, or a consequence of long term administration of drugs which induce the activity of the hepatic cytochrome P-450 enzyme system. It was recently suggested that increased aminoglycoside clearance in young drug addicts was a consequence of induction of hepatic metabolism (King et al 1985). This potential elimination route needs further exploration.…”
Section: Tobramycinmentioning
confidence: 99%